THE IMPACT OF LEARNING ORGANIZATION PRINCIPLES IN ENHANCING ORGANIZATIONAL PERFORMANCE AND QUALITY - Hrnjić, Anes; Ivaniš, Marija; Sutović, Lara (Economic Review: Journal of Economics and Business, 2025)
This study investigates the impact of learning organization principles on the performance and quality of business operations within organizations in Bosnia and Herzegovina. The research aims to identify key principles of learning organizations that significantly influence perceived business performance and quality of organizational operations, and to evaluate the extent to which organizations in Bosnia and Herzegovina can be considered learning organizations. A quantitative research approach was employed, utilizing a survey method to collect data from 154 employees who are representatives of Bosnian and Herzegovinian companies across various industries. The survey, distributed via Google Forms, measured six dimensions of learning organizations—systems thinking, shared vision, team learning and collaboration, leadership and employee empowerment, organizational culture, and learning environment—alongside four dimensions of business performance and quality—financial performance, internal processes, customer service, and learning, growth, and innovation. Descriptive statistics and regression analysis were used to analyze the data. The results revealed that shared vision, leadership and empowerment, organizational culture, and learning environment significantly and positively influence business performance and quality. However, systems thinking and team collaboration did not show statistically significant effects. The findings suggest that fostering a shared vision, empowering leadership, a supportive organizational culture, and a conducive learning environment are critical for enhancing organizational performance and quality. These insights provide valuable implications for organizations aiming to adopt learning organization principles to improve their business outcomes.